AN ALTERNATIVE APPROACH BASED ON ANGLE AND DISTANCE IN HORIZONTAL ROUTE DESIGN - Tunalioglu, Nursu; Soycan, Metin (YILDIZ TECHNICAL UNIV, 2012)
A common problem on transportation planning facilities is to generate an adequate route that refers the subsequent studies. Route design includes a process with determining the different quality alternative facilities during planning based on three dimensional field data. In this stage, the obtained route results should be taken into consideration by means of reliability and accuracy for rapid and effective decision supports. Therefore, an alternative approach is represented in this study for referring the route design with computational functions and workflow. In this approach, namely Angle-Distance search on grids, an automatic connecting algorithm of two given points due to azimuth angle of the searched points, step interval and horizontal coordinate differences to draw the zero line, which helps to perform cut fill balance due to minimizing earthwork cost, is represented. The objective function of the proposed method is the differences between the desired longitudinal grade line elevations and the computed elevations that should be done minimum. Thus, the aim is to perform cut fill balance and to make earthwork cost minimum. The feasibility and validity of the proposed method was shown in a case study by using high resolution LIDAR (Light Detection and Ranging) dataset to produce digital elevation models. The results showed that the proposed methodology could be used as a guide, which helped to minimize the total earthwork balance in route planning facilities.
Keywords: Route design; angle and distance search; optimization; grade condition; Engineering